Application of Big Data Technology for Railway Locomotive Maintenance - ZHANG Junfeng (Kongzhi Yu Xinxi Jishu)
With the evolution of railway information system and the enhancement of data acquisition ability of locomotive, a large number of parameters related to the locomotive control system and the working condition of components are recorded and stored. The application of big data technology for Shuohuang railway locomotive is possible. In view of the present situation of Shuohuang railway locomotive informationization, this paper discussed the construction, function and innovation of big data platform for locomotives, and some system functions have been applied to highlight the value of the big data technology.